Penerapan Aktivitas Social Media Marketing (SMM) pada Pemilihan Destinasi Liburan - Galuh Mira Saktiana (Akmenika: Jurnal Akuntansi dan Manajemen, 2023)
This study includes the tourism sector in particular to examine the influence of SMM (Social Media Marketing) activity, brand love, brand trust on brand equity and brand loyalty. This study adapts social network theory, the use of this theory is appropriate for this study which examines SMM activities that affect brand equity which will eventually lead to brand loyalty, because the focus that marketers want to aim for is loyalty. The brand equity can be built with high brand love and high brand trust. This study used 344 respondents to fill out a questionnaire via the Google form provided. The determination of the sample was carried out using a non-probability method with a purposive sampling technique. Then proceed with testing the validity and reliability as well as testing the hypothesis with the SEM-AMOS 22 analysis tool. The results of this study state that all hypotheses that have a direct relationship and mediation are all supported. The results of this study also show that the influence SMM activities on Brand Trust is the strongest. This means that SMM activities through platforms that are in it, such as Instagram, for example, greatly affect brand trust.